Investigation of natural environmental radioactivity concentration in soil of coastaline area of Ado-Odo/Ota Nigeria and its radiological implications - Joel, E. S. (Sci Rep, 2019)
Natural radioactivity in coastaline area soil of Ado-Odo/Ota has been carried out to ascertain the presence of radionuclides using gamma-ray spectroscopy (HPGe detector). The result showed that U-238, Th-232 and K-40 ranged from 24 ± 7–49 ± 10; 67 ± 6–120 ± 9 and 88 ± 17–139 ± 20 Bqkg(−1) respectively. The radium equivalent for the samples ranged from 132.51 to 230.91 Bqkg(−1) with mean value of 185.89 Bqkg(−1). The mean value for the gamma dose rate for the soil samples was estimated to be 81.32 nGyh(−1). The estimated values of annual effective dose equivalent ranged from 0.61 to 1.07 mSv y(−1). The estimation of alpha index representative (Iα) ranged from 0.12 to 0.24 with mean value of 0.21 while the gamma representative index ranged between 0.465 and 0.810. The activity utilization index of the soil samples ranged from 1.09 to 1.89 with mean value of 1.53. The radiological implication in the study area has shown that the soil samples with gamma dose rate value of 89.99 nGyh(−1), 94.39 nGyh(−1), 97.40 nGyh(−1) and 101.04 nGyh(−1) respectively are higher than the recommended value of 80 nGyh(−1) and may pose health implication for long term exposure.